Measuring the effectiveness of digital economy driving rural industry revitalization in Yunnan Province - Zhao, Xichao (International Journal of Social Sciences and Public Administration, 2023)
With the rapid development of digital technology and its wide penetration into various industries of economy and society, it has gradually become an important model of global concern in recent years. China’s digital economy is playing an increasingly important role in the revitalization of rural industries. Therefore, an objective and scientific evaluation of the effectiveness of digital economy driving rural industry revitalization has important theoretical and practical significance for China’s future economic development. However, in the past, most of the research on the effectiveness of digital economy driving rural industry revitalization was biased to theoretical research, and the research on how to measure the effectiveness of digital economy and rural industry revitalization was extremely rare, and there was a certain research gap. Based on previous studies on digital economy and rural industry revitalization by various scholars, this paper conducts research on the relationship between digital economy and rural industry revitalization, focusing on the rural industry revitalization in Yunnan from 2012 to 2021, and carries out analysis by means of empirical analysis through the construction of variable system. The conclusions are as follows: (1) From 2012 to 2021, the total factor productivity of rural industries in Yunnan Province is greater than 1 and is in a growing trend. Meanwhile, it can be found that the growth of total factor productivity mainly depends on technological progress. (2) Digital economy can promote the revitalization of rural industries, and through the coordinated development of digital technology and rural industries, promote the integrated development of rural industries, expand the market scale of rural industries and indirectly promote the revitalization of rural industries. Based on the above conclusions, the following political suggestions are put forward: (1) Accelerate the training of new rural industry management talents; (2) Improving the construction of digital infrastructure in rural areas; (3) Intensify research and development of rural industrial technologies